PART 1: SYLLABI FROM COURSES COVERING CLASSICAL AND MODERN SOCIAL THOUGHT - Woehrle, Lynne (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Interdisciplinary study of the great social theorists, and the progression of their ideas as they have shaped our knowledge of the behavioral sciences. Emphasis is on interpreting theory as a continuing process of understanding our world and ourselves.